Influence of micronutrients on growth and yield of coriander (Coriandrum sativum) in rainfed vertisols - T Yellamanda Reddy, Giridhar Kalidasu, C Sarada, (Journal of Spices and Aromatic Crops, 2008)
Coriander crop is grown as a rainfed rabi crop in vertisols of Andhra Pradesh. The cropgenerally suffers from periods of moisture stress from the flowering to maturity stagedepending on precipitation during November and December months. During these stressperiods, the crop shows deficiency symptoms of micronutrients such as Copper, Manganese,Zinc and Iron. The foliar application of ZnSO4 0.5%, FeSO4 0.5% and combination of ZnSO4+ FeSO4 + CuSO4 + MnSO4 all at 0.5%, had significant positive influence on all growthparameters and yield of Coriander crop. Among the treatments, ZnSO4 + FeSO4 + CuSO4 +MnSO4 all at 0.5% recorded maximum plant height, number of primary branches andsecondary branches, umbels per plant and umbellets per umbel, which are significantlysuperior to control. Crop maturity differed significantly among the treatments though thedifference between the maximum and minimum days was only 3.3 days. The treatments, ZnSO4 + Fe SO4 + Cu SO4 + Mn SO4 all at 0.5%, recorded significantly highest yield (940 kg/ha)followed by Fe SO4 0.5 % (927 kg/ha) and Zn SO4 0.5 % (922 kg/ha) which are on par witheach other and significantly superior over control (801 kg/ha).